Do Nonlinear Academic Qualifications Matter? Exploring Their Effect on Student Achievement in Primary Education - Qomariyah, Lailatul; Ni'mah, Mamluatun (Al-Qalam Institue, 2025)
This study investigates the impact of nonlinear academic qualifications among primary school teachers on student learning outcomes within the context of Islamic education in rural Indonesia. While teacher qualification alignment is widely considered a foundation of instructional quality, many schools—particularly in under-resourced areas—continue to assign teachers to subjects beyond their academic training. Employing a quantitative correlational design, this study surveyed 30 students from elementary of madrasas, using structured questionnaires, documentation, and classroom observations. Statistical analysis using Pearson product-moment correlation revealed a significant negative relationship (r = -0.512, p = 0.004) between teachers’ nonlinear qualifications and student academic performance. The coefficient of determination (R² = 0.262) indicates that approximately 26.2% of the variation in student outcomes is attributable to teacher qualification misalignment. These findings validate theoretical models of pedagogical content knowledge and reinforce prior empirical evidence emphasizing the importance of academic congruence. The results suggest an urgent need for realignment of teacher recruitment and placement policies to ensure subject specialization, particularly in rural schools. While academic nonlinearity is not the sole factor influencing learning, it remains a meaningful structural concern. The study recommends targeted retraining, curriculum responsiveness in teacher education, and further research into mediating variables such as teaching experience and institutional support.